(untitled) (Journal of Pharmaceutical Negative Results, 2020)
Atherosclerotic Cardiovascular Disease (ASCVD) is a commoncause of morbidity and mortality and can impose a high budgetto all health services. The American College of Cardiology/American Heart Association (ACC/AHA) recommendedthe initiation of high-intensity statin therapy in patients withclinical ASCVD regardless of baseline low-density lipoproteincholesterol (LDL-C) levels.[1] Statin, a commonly and effectivetherapy for dyslipidemia besides diet and exercise introducedby Merck in November 1986 as the New Drug Application tothe US Food and Drug Administration (FDA) and lovastatin,was approved by FDA to become the first commercial statinin September 1987.[2]